Valproic Acid and the Liver Injury in Patients with Epilepsy: An Update - Guo, Hong-Li; Jing, Xia; Sun, Jie-Yu; Hu, Ya-Hui; Xu, Ze-Jun; Ni, Ming-Ming; Chen, Feng; Lu, Xiao-Peng; Qiu, Jin-Chun; Wang, Tengfei (Current pharmaceutical design, 2019)
Valproic acid (VPA) as a widely used primary medication in the treatment of epilepsy is associated with reversible or irreversible hepatotoxicity. Long-term VPA therapy is also related to increased risk for the development of non-alcoholic fatty liver disease (NAFLD). In this review, metabolic elimination pathways of VPA in the liver and underlying mechanisms of VPA-induced hepatotoxicity are discussed. We searched in PubMed for manuscripts published in English, combining terms such as "Valproic acid", "hepatotoxicity", "liver injury", and "mechanisms". The data of screened papers were analyzed and summarized. The formation of VPA reactive metabolites, inhibition of fatty acid β-oxidation, excessive oxidative stress and genetic variants of some enzymes, such as CPS1, POLG, GSTs, SOD2, UGTs and CYPs genes, have been reported to be associated with VPA hepatotoxicity. Furthermore, carnitine supplementation and antioxidants administration proved to be positive treatment strategies for VPA-induced hepatotoxicity. Therapeutic drug monitoring (TDM) and routine liver biochemistry monitoring during VPA-therapy, as well as genotype screening for certain patients before VPA administration, could improve the safety profile of this antiepileptic drug.